Fossil climbing perch and associated plant megafossils indicate a warm and wet central Tibet during the late Oligocene - Feixiang Wu (Nature Portfolio, 2017)
Abstract Understanding the Tibetan Plateau’s palaeogeography and palaeoenvironment is critical for reconstructing Asia’s climatic history; however, aspects of the plateau’s uplift history remain unclear. Here, we report a fossil biota that sheds new light on these issues. It comprises a fossil climbing perch (Anabantidae) and a diverse subtropical fossil flora from the Chattian (late Oligocene) of central Tibet. The fish, Eoanabas thibetana gen. et sp. nov., is inferred to be closely related to extant climbing perches from tropical lowlands in south Asia and sub-Saharan Africa. It has osteological correlates of a labyrinth organ, which in extant climbing perches gives them the ability to breathe air to survive warm, oxygen-poor stagnant waters or overland excursion under moist condition. This indicates that Eoanabas likewise lived in a warm and humid environment as suggested by the co-existing plant assemblage including palms and golden rain trees among others. As a palaeoaltimeter, this fossil biota suggests an elevation of ca. 1,000 m. These inferences conflict with conclusions of a high and dry Tibet claimed by some recent and influential palaeoaltimetry studies. Our discovery prompts critical re-evaluation of prevailing uplift models of the plateau and their temporal relationships with the Cenozoic climatic changes.